Environmental Factors Associated With Type 1 Diabetes - Esposito, Susanna; Toni, Giada; Tascini, Giorgia; Santi, Elisa; Berioli, Maria Giulia; Principi, Nicola (Frontiers in Endocrinology, 2019)
Type 1 diabetes (T1D) is a chronic autoimmune disorder that leads to progressive pancreatic ß-cell destruction and culminates in absolute insulin deficiency and stable hyperglycaemia. It is very likely that environmental factors play a role in triggering islet autoimmunity. Knowing whether they have true relevance in favouring T1D development is essential for the effective prevention of the disease. Moreover, prevention could be obtained directly interfering with the development of autoimmunity through autoantigen-based immunotherapy. In this narrative review, the present possibilities for the prevention of T1D are discussed. Presently, interventions to prevent T1D are generally made in subjects in whom autoimmunity is already activated and autoantibodies against pancreatic cell components have been detected. Practically, the goal is to slow down the immune process by preserving the normal structure of the pancreatic islets for as long as possible Unfortunately, presently methods able to avoid the risk of autoimmune activation are not available. Elimination of environmental factors associated with T1D development, reverse of epigenetic modifications that favour initiation of autoimmunity in subjects exposed to environmental factors and use of autoantigen-based immunotherapy are possible approaches, although for all these measures definitive conclusions cannot be drawn. However, the road is traced and it is possible that in a not so distant future an effective prevention of the disease to all the subjects at risk can be offered.